Applications of Solar Energy - Tyagi, Himanshu; Agarwal, Avinash Kumar; Chakraborty, Prodyut R.; Powar, Satvasheel (Energy, Environment, and Sustainability, 2018)
XVII, 364 p. 189 illus., 133 illus. in color.